Genetic Purity Test using SSR Markers in Pigeon Pea - RAKESH C MATHAD; AS CHANNAVEERASWAMY; RUDRA NAIK; D VINOD KUMAR; SA ASHTAPUTRE (Seed Research, 2026)
Pigeon pea is one of the strategic and vital dry land crops having significance in food grain sustainability and nutrition. The seed testing especially genetic purity assumes greater importance in quality seed availability to the farmers. The present investigation aims at developing faster method using molecular methods using simple sequence repeat (SSR) markers for ten varieties of pigeon pea (Maruti, TS3R, GRG-811, Asha, BSMR-736, GRG833, GC-11-39, WRP-1, ICPL-87 and Bannur local). Forty three SSR markers were used to distinguish ten pigeon pea varieties with average 2.81 alleles per marker. Out of which sixteen markers were polymorphic to these ten varieties having PIC values ranging from 0.567 to 0.695. The variety specific markers viz.,CcM0039 (GC-11-39), CcM0047 (GRG-833), CcM0057 (Maruti), CcM0082 (GRG-811), CcM0093 (Bannur Local), CcM0095 (GC-11-39), CcM0133 (Maruti), CcM0185 (WRP-1), CcM0193 (GRG-833), CcM0248 (WRP-1), CcM0252 (ICPL-87), CcM0257 (ICPL-87), CcM0271 (BSMR-736), CcM0293 (TS3-R), AHSSR46 and AHSSR48 (Asha) were used for conducting molecular genetic purity tests. The cluster analysis of all the ten pigeon pea varieties based on the morphological characters and SSR markers revealed differences in the cluster pattern. There were only two clusters based on the morphological scoring of characters but three clusters using SSR markers by fixed Dice similarity coefficient of 3.71. These tests were further validated by field grow out test. The correlations of field grow out test and molecular genetic purity by paired t-test with calculated t-value (1.66) less than the table value (2.26) showing no significant differences between these two methods. Also there is positive correlation exist between these two methods (r = 0.77).